Analisis permukaan dan keliangan penapis molekul renium-MCM-41 - Salasiah Endud; Zainab Ramli, 1959-; Halimaton Hamdan, 1956-; Lee, Kwong Seng; Simposium Kimia Analisis Malaysia (ke-12 : 1999 : Kuala Trengganu, Terengganu) (Skudai : Universiti Teknologi Malaysia, 1999)
50